TINGKAT STRES DAN KECEMASAN DALAM MENGHADAPI UJIAN MATEMATIKA - Minta Ito Simamora Simamora; Ulfa Ulfa Annisa Lubis; Eka Putri Yani; Dini Aulia (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to analyze the level of stress and anxiety among students in facing mathematics exams. The method used is descriptive quantitative with a survey technique involving 11 students. The research instrument was a Likert-scale questionnaire. The results show that most students experience anxiety and stress due to academic pressure, difficulty of material, and lack of preparation time. Social support also plays a role in reducing this pressure. This study suggests the need for stress management strategies and supportive instructional approaches in mathematics learning.